Strategy and practice for sustainability in businesses in the Middle East and North Africa in a global perspective - Ayman Ismail; Fatima Boutaleb; Esra E. Karadeniz; Ehud Menipaz; Chafik Bouhaddioui; Widad Ali Abdel Rahman; Lidia Sanchez-Ruiz; Thomas Schøtt (Journal of Risk and Financial Management, 2022)
A business may adopt a strategy for sustainability and may implement its strategy in its practice. Our question is, how are strategy and practice coupled and shaped by entrepreneurs and businesses embedded in national eco-systems in the Middle East and North Africa and around the world? Businesses were randomly sampled and surveyed in 2021, and national conditions were assessed by experts in ten countries in the Middle East and North Africa and in Spain and other countries around the world, as part of the Global Entrepreneurship Monitor. Strategy and practice are found to have a loose coupling but are tighter in the Middle East and North Africa than in Spain. Strategy is promoted by support from businesses and governments, but support depends on national wealth. Strategy and practice by entrepreneurs and businesses are promoted by the entrepreneurs' human and social capital and the value of making a difference in the world and continuing a family tradition. Findings contribute to understanding business engagement with sustainability, specifically in the Middle East and North Africa, as compared to Spain and in a global perspective.
Keywords: 650; businesses; Global Entrepreneurship Monitor; Middle East and North Africa; practice; strategy; sustainability